Vasomotor Symptoms Resulting From Natural Menopause: A Systematic Review and Network Meta-analysis of Treatment Effects From the National Institute for Health and Care Excellence Guideline on Menopause. Issue 12 (December 2017) - Sarri, G.; Pedder, H.; Dias, S.; Guo, Y.; Lumsden, M. A.
Abstract : (Abstracted from BJOG 2017;124:1514–1523) Vasomotor symptoms (VMSs)—the most common menopausal symptoms—occur in approximately 75% of postmenopausal women in the United Kingdom and are severe in 25%. A large number of treatments, both pharmacological and nonpharmacological, have been used to relieve VMSs during menopause.